Estimation of level of maintenance of quality of services of car-care center - Кузьмін, Віктор Степанович (Technology audit and production reserves, 2012)
The model and system of maintenance of quality of services of the enterprise of car-care centre is developed. Requirements and conditions of formation of system of an estimation of level of maintenance are considered and defined, the general technique and an estimation order is presented. Recommendations about definition of factor of quality of maintenance of production and service are resulted